The influence of sustainable supply chain management on circular economy capabilities in MSMEs in the fashion and cosmetics industries - Theresia Mayke Nindiya; Ratih Dyah Kusumastuti (Kemakmuran Hijau: Jurnal Ekonomi Pembangunan, 2026)
Background: The adoption of circular economy principles offers significant opportunities for micro, small, and medium enterprises (MSMEs) in Indonesia, particularly because of their close interaction with consumers who generate post-consumption waste. This study examines how sustainable supply chain management contributes to the development of circular economy capabilities among MSMEs operating in the fashion and cosmetics sectors. Methods: Data were collected from 72 MSMEs located in Java and Bali that had implemented at least one of the 3R practices (reduce, reuse, or recycle). The relationships among variables were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings: The analysis revealed that green supply chain management and sustainable supply chain design positively contribute to circular economy capabilities. In addition, supply chain relationship management affects circular economy capabilities indirectly through its influence on sustainable supply chain design. Conclusion: Sustainable supply chain practices play an important role in strengthening the ability of MSMEs to adopt circular economy principles. The results highlight the need for integrated supply chain strategies to support sustainable business transformation within the fashion and cosmetics industries. Novelty/Originality of this article: This study extends the circular economy literature by providing empirical evidence from Indonesian MSMEs and demonstrating both direct and indirect pathways through which sustainable supply chain management enhances circular economy capabilities.